2023
DOI: 10.1111/iep.12475
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression and role of MicroRNA‐214‐3p/SLC8A1 in neonatal Hypoxic‐Ischaemic encephalopathy

Abstract: Neonatal hypoxic-ischaemic encephalopathy (HIE) refers to brain damage caused by intra-uterine distress and asphyxia/hypoxia during the perinatal and neonatal periods. MicroRNA (MiR)-214-3p plays a critical role in cell growth and apoptosis. The aim of this study was to investigate the expression and role of miR-214-3p in neonatal HIE development, and to explore the underlying mechanisms. The expression of miR-214-3p was significantly down-regulated, while that of Slc8a1, a direct target of miR-214-3p, was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The calcium extrusion regulatory molecule, SLC8A1, encodes a member protein of the NCX1 antiporter that is activated by protein phosphatase 2A. This protein facilitates the transport of calcium out of cells and sodium into cells, thereby regulating calcium homeostasis [38,39]. Numerous studies have reported an association between SLC8A1 and various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The calcium extrusion regulatory molecule, SLC8A1, encodes a member protein of the NCX1 antiporter that is activated by protein phosphatase 2A. This protein facilitates the transport of calcium out of cells and sodium into cells, thereby regulating calcium homeostasis [38,39]. Numerous studies have reported an association between SLC8A1 and various diseases.…”
Section: Discussionmentioning
confidence: 99%